The Economic and Safety Improvement Feasibility of Urban Ocean Fishing Port Modernization – Study Case of Nizam Zachman - Andojo Wurjanto; Julfikhsan Ahmad Mukhti; Aisyah Diah Larasati; Maria Utami Manullang (Journal of Engineering and Technological Sciences, 2023)
The Nizam Zachman Jakarta Ocean Fishing Port (PPSNZJ), the largest fishing port in Indonesia, is currently experiencing overcapacity. This results in ships being moored in rows parallel to berths, indicating the insufficient number of berths in the port. This configuration poses a safety hazard due to the proximity of the moored ships, making it challenging to evacuate them in the event of a fire or other natural disasters. This study was conducted to propose an alternative concept for facility development in urban ocean fishing ports, with PPSNZJ as a study case. The study included a site visit to understand the actual berthing configuration of ships, data collection from the port technical execution unit, and observation of existing fish cargo handling operations. The collected data was analyzed to determine berth capacity and storage productivity, which was used to calculate the number of additional berths required to accommodate loading, unloading, and mooring ships. Based on the design calculations, an alternative development layout is proposed, which fulfils the berth capacity and safety requirements. This study also revealed that the development cost is relatively competitive compared to similar projects.